The approach by Badi’uzzaman Said Nursi towards non-Muslim rights in the Risalah al-Nur - Ismail, Masthurhah; Fatah Yasin, Raudlotul Firdaus; Jaapar, Khafizatunnisa’ (University Melaka Publisher, 2023)
The Non-Muslim rights in an Islamic state have been recognized by Islam since the time the Prophet Muhammad SAW was sent to spread the Message of Islam. However, the rights reserved for them are not absolute; in fact Islam has outlined certain guidelines to limit the freedom allocated to them, to which they are bound. This paper focuses on the approach adopted by Badiuzzaman Said al-Nursi in his treatise Risalah al-Nur, towards the rights of Non-Muslims in an Islamic country. This paper is categorized as a library research. The framework specifically utilizes two main methods namely the data collection method and the data analysis method encompassing analyses of historical records, content analysis, and biographical analysis. A review of the Risalah al-Nur reveals that its approach towards the Non-Muslim rights in an Islamic state is that of a pacifist nature, based on the principles of justice. In short, this approach may be implemented in a country comprising plural societies practicing a variety of religious beliefs such as Malaysia. The right to practice religion for the Non-Muslims is guaranteed because the views of ulamas like Badiuzzaman Said Nursi are not grounded on whims and fancy but founded on schools of thoughts driven by the Islamic law as well as by firm evidences and rational analogies. The approach preached by this scholar is vital in the current context and must be expressed as a holistic approach.